Determination of biomass co-combustion process state based on flame image series analysis - Kotyra, A.; Wójcik, W.; Gromaszek, K. (Штучний інтелект, 2017)
The article presents an approach to use some base frequency parameters of flickering such as the frequency having the largest amplitude (base frequency) and centroid of amplitude spectrum for characterization of different combustion process state. The laboratory test stands enabled scaled down 10:1 combustion conditions. Analysis results show that the frequency spatial information could be helpful in combustion process diagnostics. У статті запропоновано підхід до використання параметрів базової частоти мерехтіння, таких як базова частота та центроїд амплітудного спектра для характеристики різних станів процесів згоряння. Стенд лабораторного випробування дозволив знизити умови горіння 10:1. Результати аналізу показують, що просторова інформація частоти може бути корисною для діагностики процесу згоряння.